PENGARUH MARGARIN DAN MINYAK KELAPA SAWIT DENGAN PEMANASAN BERULANG TERHADAP KADAR INSULIN DARAH PUASA PADA TIKUS WISTAR - Retno Larasati; Bambang Wirjatmadi; Merriyana Adriani (Universitas STRADA Indonesia, 2016)
Margarine and coconut oil is a food that is commonly consumed by the population of Indonesia, both these foods are a source of trans fatty acids that can induce insulin resistance that eventually causes hyperinsulinemia. This study aims to analyze the differences in fasting blood insulin levels among both the control group and the treatment that is given Trans Fatty Acid (ma rgarine and palm oil with repeated heating). Method used purely experimental approach Post Test Only Control Group Design. Samples used 25 male Wistar strain rats were divided into 5 groups. The collection of data obtained from the results of laboratory examinations of fasting blood insulin. Research results from the test with one way Anova with a confidence level of 95%. The result showed fasting insulin levels between the two groups did not differ significantly. It was concluded that margarine and palm oi l with repeated heating does not cause hyperinsulinemia, but the group given both these foods showed a tendency to increased levels of fasting blood insulin